EFFECT OF INNOVATIVE INTERVENTION IN ELIMINATING STIGMA AND DISCRIMINATION AMONG PEOPLE LIVING WITH AIDS IN KHARTOUM STATE, SUDAN 2013 - Mohamed Osman Elamin; Hatim Rahamtalla Mohamed Ahmed; Fatima Fadul Ali (European Scientific Journal, ESJ, 2015)
Since the outbreak of the epidemic, almost 78 million people have been infected with the HIV virus and about 39 million people have died of HIV. Globally, 35.0 million people were recorded to be living with HIV at the end of 2013. Sub-Saharan Africa remains the most severely affected region, and accounts for almost 71% of the people living with HIV worldwide12. HIV/AIDS cases in Sudan increases gradually from one case in 1986 to 10444 cases in 2009, to about 0.67% 13. People living with the disease are the main source through which HIV is spreading. They suffer social stigma and community discrimination. Information, Education, and Communication (IEC) are public health approach aim in changing or reinforcing health-related behaviors to a target audience through communication methods and principles 1. A quasi-experimental study was conducted in Khartoum State, which aim to study the effect of information, education, and communication in reducing stigmatization and discrimination among people living with AIDS/HIV (PLWAIDS/HIV). 25 participants of the total registered members of PLWAIDS/HIV in the society have been selected by systematic random sampling. An intensive intervention using IEC was conducted for six months. Data which were collected before and after the intervention were compared and analyzed using Chi-square test through a computer using SPSS Program. Furthermore, this was presented in tables and graphs. The study revealed that there was a significant elimination of social stigma and a slight decrease in the feeling of community discrimination. The IEC strategy has been proven to be effective in a significant elimination of social stigma and has slightly decreased the feeling of community discrimination.